Pengaruh Variasi pH Terhadap Pelepasan Monomer dari Resin Komposit Nanofiller - Prisca Dhyaning Dentiana; Siti Sunarintyas; Widowati Siswomihardjo (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Nanofilled composite resin is a kind of composite thatis used for restorative material. Nanofilled composite resin has nanometer sized silica filler, providinghigh level of aesthetic and refinement properties. Monomerbis-GMA, UDMA dan TEGDMA from composite resincan be releasedwhen in contact with oral fluid. Concentration of monomer release may affect the biocompatibility of composite resin. The objective of this studywas to determine the effect of pH variation on monomer release of nanofilled composite resin.The samples used were nanofilled composite resin Filtek Z250XT (3M ESPE, Seefeld, Germany). Twelve samples with size of 6 x 4 x 2 mm were divided into three groups and then soaked into solution of ± pH 3.5 (citric acid), ± pH 7 (distilled water), and ± pH 8 (sorensen’s phosphate) for 7 days. After 7 days of immersion, eachof the solutions was analyzed using HPLC to determine the concentration of monomer release. Monomer was analyzed using a mobile phase of acetonitrile and water with ratio of 7:3, flow rate 1 ml/min at room temperature. The column used was C18 5 µm, 125 mm in length and 4 mm in diameter. The wavelength used was 220 nm. Data were statistically analyzed usingONE-WAY ANOVA. The means concentration of monomer release (µg/ml) on the three pH groups were 2.97 ± 1.13; 1.50 ± 0.67; and 4.07 ± 0.91. Results of ONE-WAY ANOVA showed that there were differences between means concentration of monomer release from the three groups (ρ<0.05). The conclusion of this study wasthe immersion of nanofilled composite resin in an acid solution and alkaline solution increased thebis-GMAmonomer release from nanofilled composite resin.